2020
DOI: 10.1111/pcn.12985
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant limbic brain structures in young individuals at risk for mental illness

Abstract: Aim Alterations in limbic structures may be present before the onset of serious mental illness, but whether subfield‐specific limbic brain changes parallel stages in clinical risk is unknown. To address this gap, we compared the hippocampus, amygdala, and thalamus subfield‐specific volumes in adolescents at various stages of risk for mental illness. Methods MRI scans were obtained from 182 participants (aged 12–25 years) from the Canadian Psychiatric Risk and Outcome study. The sample comprised of four groups:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
(70 reference statements)
1
18
1
Order By: Relevance
“…The results of our ROC analyses suggest that the right hippocampal volume is a potential marker for differentiation between SZ and BD. To this end, multimodal functional neuroimaging studies [26,[51][52][53][54][55][56][57][58][59][60][61] that combine structural MRI [3,16,[18][19][20][21]23,[26][27][28][42][43][44]51,[61][62][63], functional MRI [26,[53][54][55][56][57][58][59][60][61]64,65], magnetic resonance spectroscopy [66][67][68][69], positron emission tomography [69][70][71][72], elec...…”
Section: Discussionmentioning
confidence: 99%
“…The results of our ROC analyses suggest that the right hippocampal volume is a potential marker for differentiation between SZ and BD. To this end, multimodal functional neuroimaging studies [26,[51][52][53][54][55][56][57][58][59][60][61] that combine structural MRI [3,16,[18][19][20][21]23,[26][27][28][42][43][44]51,[61][62][63], functional MRI [26,[53][54][55][56][57][58][59][60][61]64,65], magnetic resonance spectroscopy [66][67][68][69], positron emission tomography [69][70][71][72], elec...…”
Section: Discussionmentioning
confidence: 99%
“…7,28,29 These findings support the pathological model of schizophrenia that the patients have neurodevelopmental abnormalities but also exhibit active gray matter loss mainly in the frontal and temporo-limbic regions in the initial years around the onset, which may underlie the first manifestation of positive symptoms. Further research is needed on other morphological characteristics (e.g., gyrification and sulcus pattern) 51,52 and subcortical structures 53,54 in the various clinical stages of schizophrenia.…”
Section: Brain Mri Findings In Schizophrenia Through the Life Coursementioning
confidence: 99%
“…In contrast to the QSM results, there were no associations between brain volume and behaviour. This differs from research on mental health and brain structure in unexposed participants that has found associations between caudate volume, putamen development, amygdala, hippocampus, and thalamus abnormalities and internalizing and externalizing disorders [14][15][16][17][18][19][20][21][22]. Only one study on children with PAE found a trend-level association between caudate volume and internalizing symptoms [52].…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, externalizing disorders such as attention-deficit/hyperactivity disorder (ADHD) and oppositional defiant disorder are 10 and 13 time more common than in the general population [13]. Unexposed youth and adults with internalizing (depression and anxiety) and externalizing (ADHD) disorders tend to show volumetric abnormalities of limbic and basal ganglia structures [14][15][16][17][18][19][20][21][22]. Youth with PAE have similar volumetric abnormalities [23][24][25]; however, little research has investigated the neural underpinnings between brain and internalizing or externalizing symptoms in individuals with PAE.…”
Section: Introductionmentioning
confidence: 99%